IDOPS, a Profile HMM-Based Tool to Detect Pesticidal Sequences and Compare Their Genetic Context - Díaz-Valerio, Stefani; Lev Hacohen, Anat; Schöppe, Raphael; Liesegang, Heiko (Frontiers in Microbiology, 2021)
Biopesticide based crop protection is challenged by insect resistance. Thus the constant expansion of available biopesticides is crucial for sustainable agriculture. Although Bacillus thuringiensis is the major agent for pesticide bioprospection, the number of bacteria species synthesizing proteins with biopesticidal potential is much higher. The Bacterial Pesticidal Protein Resource Center (BPPRC) offers a database of sequences for control of insect pests, grouped in structural classes. Here we present IDOPS, a tool to detect novel biopesticidal sequences and analyze them within their genetic environment. The backbone of IDOPS detection unit is a curated collection of high-quality hidden Markov models that is in accordance with the BPPRC nomenclature. IDOPS was positively benchmarked with BtToxin_Digger and Cry_Processor. In addition, a scan of the UniProtKB database with IDOPS models returned abundant new candidates to pesticidal proteins distributed in all of the structural groups. Gene expression depends on the genomic environment, therefore, IDOPS provides a comparative genomics module to investigate the genetic regions surrounding pesticidal genes. This feature enables the investigation of accessory elements and evolutionary traits relevant for optimal toxin expression and functional diversification. IDOPS contributes to study and expand our current arsenal of pesticidal proteins used for crop protection.